Research Traditions in Islamic Education: An Integrative Perspective - Susanti, Riri; Semiarni, Zulfani; Mukhtar, Dertha; M., Amril Huda (El-Rusyd, 2025)
This study analyzes research traditions and methodological models in Islamic education grounded in three major foundations empirical, historical, and normative and proposes an integrative research model to address the complexity of contemporary educational challenges. Each research tradition is characterized by distinct epistemological assumptions, analytical orientations, and methodological contributions, which necessitate a critical examination of their respective strengths and limitations. Employing a qualitative descriptive-analytical approach, this study is based on a literature review of books, peer-reviewed journal articles, and relevant scholarly documents. The analysis involves conceptual classification, critical evaluation of research models, and synthesis of interrelationships among research traditions. The findings indicate that the empirical tradition provides an objective basis through measurable data, the historical tradition offers contextual understanding through source criticism and reconstruction of educational development, while the normative tradition establishes philosophical and value-based foundations derived from the Qur’an, hadith, and classical Islamic scholarship. However, when applied in isolation, each tradition reveals methodological limitations. Therefore, this study emphasizes the urgency of an integrative research model that synthesizes empirical, historical, and normative dimensions to produce more holistic, relevant, and applicable analyses in Islamic education research. This integrative framework contributes methodologically to the development of Islamic education studies, particularly in curriculum design, instructional models, educational policy, and the reinforcement of Islamic values in educational practice.